Paradigm shift in vertebral eosinophilic granuloma - Özbek, Muhammet Arif; İpek, Veyselkarani; Dinç, Cem (My University, 2023)
Objective: Eosinophilic granuloma is the most common type of Langerhans cell histiocytosis. Vertebral bone involvement of eosinophilic granuloma is a rare disease. There are few studies in the literature on patients with vertebral bone involvement diagnosed with eosinophilic granuloma. There is still no clear protocol for the treatment of patients with vertebral involvement with eosinophilic granuloma. This article is a summary of the clinical follow-ups of our 6 cases diagnosed with spinal eosinophilic granuloma. We changed the chemotherapy protocol or extended the duration of chemotherapy in patients with progressive disease. Methods: In this study, there are six patients (4 male and 2 female) with vertebral involvement of eosinophilic granuloma in our hospital between September 2017 and August 2022. The clinical findings, radiological images, treatments and follow-up results of the patients were analyzed retrospectively. Results: In the follow-ups, a new vertebral bone involvement was observed in two patients and a femoral bone involvement was observed in another patient. One patient with neurological deficit underwent surgical treatment. Chemotherapy treatment was given to four patients with multiple bone involvement or recurrence. No recurrence was observed in three patients who started chemotherapy treatment after recurrence. Conclusions: Surgical treatment should be considered in patients with neurological deficits and spinal instability. According to the results of our study, patients with multiple bone or systemic involvement and no neurological deficit should receive chemotherapy treatment. We recommend changing the chemotherapy protocol or extending the chemotherapy duration in patients with progressive disease.
Keywords: Eosinophilic Granuloma; Spine; Treatment